"Because There Are Young Women Behind Me": Learning from the Testimonios of Young Undocumented Women Advocates. Issue 2 (1st June 2020) - Silva, Carolina
Abstract: In this article, I discuss the experiences of young undocumented Latinas, aged between 19 and 22, in a university support and advocacy group for undocumented students. While recent research has investigated the advocacy of undocumented youth, there is a lack of attention on the experiences of undocumented women who advocate. To address this gap, I center the testimonios (testimonies) of five young undocumented women to examine their advocacy experiences. As a result of advocacy, the young women gained visibility as immigrant youth leaders, created a pipeline of support for other young undocumented women leaders, and faced disapproval from educators. I conclude by suggesting that schools and educators can foster the leadership of young undocumented women and acknowledge advocacy as a legitimate tool for social justice in education settings.